El Departamento de Turismo. Una institución precursora del fomento turístico en Chile (1929-1942) - Yáñez Andrade, Juan Carlos (2022)
This article analyzes the origins and development of the Department of Tourism, created during the administration of Carlos Ibáñez del Campo (1927-1931). The Department of Tourism falls under the Ministry of Development and originated within the context of the Tourism Promotion Law of 1929; its powers were directed towards the promotion and inspection of tourism activities. It is argued that the creation of the Department of Tourism is framed in a strategic vision of the State of Chile that understands the tourism as a central economic activity, way for the modernization of the country and source of fiscal revenue.